Efficient synthesis of ningalin C - Anucha Namsa-Aid (2018)
(Matrix presented) A concise and efficient synthesis of the permethyl derivative of the marine alkaloid ningalin C (2) has been accomplished. The key step involves the formation of a pyrrolinone fron an aminoquinone in one pot. An efficient route for the synthesis of the key aminoquinone has also been developed.